Matematica e scrittura digitale del mondo (Nóema, 2025)
Mathematics and digital writing of the worldIn the context of the current transcription of the world through digital technologies, this essay aims to investigate its conditions and possibilities by means of a genealogy of the formal thought that has enabled A mathematical writing of the concept of “limit”. In the first part, we show from an historical perspective the contribution of the formal writing of the limit to the operational mediation between finite and infinite as a decisive condition for the scientific revolution of knowledge and technology. In the second part, the gaze is broadened to a horizon that links ancient and modern, reconnecting to the problem of incommensurables, showing how the concept of limit is a paradigm of the way in which mathematical writing places itself on the frontier of the visible and the known, forcing the boundaries of the maps of knowledges traced so far. In the third part, the peculiarity of the digital writing of the world is investigated as an emblematic product of this tradition of formal writing.
Keywords: Philosophy of Mathematics; Language; Philosophy of Digital; Artificial Intelligence; Genealogy of Mathematical Concepts; Number; Formal Thought; Algebra; Leibniz; Infinite; Limit; Scientific Revolution